2019
DOI: 10.1038/s41467-019-10967-7
|View full text |Cite
|
Sign up to set email alerts
|

ZRANB3 is an African-specific type 2 diabetes locus associated with beta-cell mass and insulin response

Abstract: Genome analysis of diverse human populations has contributed to the identification of novel genomic loci for diseases of major clinical and public health impact. Here, we report a genome-wide analysis of type 2 diabetes (T2D) in sub-Saharan Africans, an understudied ancestral group. We analyze ~18 million autosomal SNPs in 5,231 individuals from Nigeria, Ghana and Kenya. We identify a previously-unreported genome-wide significant locus: ZRANB3 (Zinc Finger RANBP2-Type Containing 3, lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 72 publications
(78 reference statements)
0
64
0
Order By: Relevance
“…Such study should preferably also include neighboring Horn of African populations, including Djibouti and Eritrea, for whom there are no or little genomic data available. To explore mechanisms involving disease alleles or pharmacogenetic variants, approaches recently reported by Adeyemo et al 7 will be useful to employ.…”
Section: Discussionmentioning
confidence: 99%
“…Such study should preferably also include neighboring Horn of African populations, including Djibouti and Eritrea, for whom there are no or little genomic data available. To explore mechanisms involving disease alleles or pharmacogenetic variants, approaches recently reported by Adeyemo et al 7 will be useful to employ.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent genome-wide analysis on genetic susceptibility to type 2 diabetes (T2D) in sub-Saharan Africans from Nigeria, Ghana and Kenya, identified a previously-unreported genome-wide significant locus that is specific to African populations (and monomorphic in European and Asians), while the same study showed transferability of 32 established T2D loci. 23 Taken together, the underrepresentation of Africans in international genetic research and variation databases, combined with the greater genetic diversity in African populations, results in some reported variants in genes that are included on the consensus lists may not cause disease in Africans, whilst actual pathogenic variants not yet reported from African populations may not have been considered or included. Also, African genomic studies risk identifying many variants of unknown significance that will likely turn out to be benign.…”
Section: What Results To Return?mentioning
confidence: 99%
“…We selected 10 candidate MRs for experimental validation based on their activity in T2D-enriched clusters and their association with diabetes susceptibility loci in GWAS studies. They included: AFF3 40 , BACH2 41 , BNC2 42 , GAS7 43 , MYT1L 44 , NFATC3 45 , RFX7 46 , TSHZ2 47 , ZRANB3 48 , and ZNF385D 49 . Critically, their mRNA expression was not significantly different based on scRNA-seq analysis, suggesting that these proteins could not have been identified using more traditional approaches (Supplementary Data 3).…”
Section: Resultsmentioning
confidence: 99%